Research Fraud: Methods For Dealing With An Issue That Negatively Impacts Society’s View Of Science - Greenbaum, Dr. Dov (Science and Technology Law Review, 2009)
Like the legal and medical professions, the relatively insular academic scientific community has always preferred to deal with instances of misconduct quietly, without external intervention. Recent highly publicized instances of scientific misconduct have shocked the community, renewing calls for alternative approaches to address this growing threat to science’s position of trust within society, and consequently the public’s generous funding of academic research. Science‘s inability to effectively define the outer boundaries of misconduct, coupled with a lack of ethics education and enforcement, has led to the current situation. This article examines the current level of fraud and enforcement and suggests some policy alternatives to the status quo. This article first presents a novel tiered structure based on a simple analysis of two basic components of any instance of scientific misconduct, to provide a method to discriminate between different levels of misconduct. Next, this article looks to a number of authorities and institutions that could educate current and future scientists about the nature and effects of fraud in scientific research. Finally, this article explores options for enforcing and punishing instances of misconduct, including both civil and criminal, particularly mindful of the devastating career implications resulting from any association with an investigation of misconduct. In this vein, First Amendment and due process issues are highlighted and examined. This article concludes that, given the devastating repercussions to even exonerated scientists, a criminal code that takes into account the particular concerns of the scientific community would best provide protection for scientists and promote a more ethical scientific community.